The Dark Path The Structure of War and the Rise of the West - Murray, Williamson (Yale University Press, 2024)
From an esteemed military historian, a sweeping history of the revolutions in war-fighting that have shaped the modern world   Heraclitus wrote that "war is the father of all," and it has formed much of the modern world. Although the fundamental nature of war has not altered over the centuries, constant change, innovation, and adaptation have repeatedly reshaped how wars are fought in the West. Revolutions in military practice cannot be separated from larger social developments in areas like logistics, finance and economics, and the culture of military organizations.   In The Dark Path, Williamson Murray argues that the history of warfare in the West hinged on five revolutions, which both reflected the social, political, and economic conditions that produced them and in turn influenced how those conditions evolved. These five key turning points are the advent of the modern state, which formed bureaucracies and professional militaries; the Industrial Revolution, which produced the financial and industrial means to sustain and equip large armies; the French Revolution, which provided the ideological basis needed to sustain armies through continent-sized wars; the merging of the Industrial and French Revolutions in the U.S. Civil War; and the accelerating integration of technological advancement, financial capacity, ideology, and government that unleashed the modern capacity for total warfare.   An ambitious work of synthesis, this book shows how the world continually re-creates war-and how war, in turn, continually re-creates the world
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Oct 2024)
Keywords: HISTORY / Military / General